2008
DOI: 10.1051/0004-6361:200810625
|View full text |Cite
|
Sign up to set email alerts
|

Transiting exoplanets from the CoRoT space mission

Abstract: Context. The CoRoT space mission routinely provides high-precision photometric measurements of thousands of stars that have been continuously observed for months. Aims. The discovery and characterization of the first very massive transiting planetary companion with a short orbital period is reported. Methods. A series of 34 transits was detected in the CoRoT light curve of an F3V star, observed from May to October 2007 for 152 days. The radius was accurately determined and the mass derived for this new transit… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
183
1

Year Published

2009
2009
2020
2020

Publication Types

Select...
5
4

Relationship

4
5

Authors

Journals

citations
Cited by 209 publications
(191 citation statements)
references
References 39 publications
(41 reference statements)
7
183
1
Order By: Relevance
“…The authors showed that HD 33636 b is not in the planet domain and is indeed an M dwarf. On the other hand and surprisingly enough, the CoRoT space mission found a 21.66-M Jup transiting brown dwarf with a 4.26-day period Deleuil et al (2008).…”
Section: Concluding Discussionmentioning
confidence: 96%
“…The authors showed that HD 33636 b is not in the planet domain and is indeed an M dwarf. On the other hand and surprisingly enough, the CoRoT space mission found a 21.66-M Jup transiting brown dwarf with a 4.26-day period Deleuil et al (2008).…”
Section: Concluding Discussionmentioning
confidence: 96%
“…Collier Pollacco et al 2008;Hebb et al 2008), by HAT (Bakos et al 2007), and by the CoRoT space mission (e.g. Barge et al 2008;Bouchy et al 2008;Moutou et al 2008;Deleuil et al 2008;Rauer et al 2009), as well as the parameters of these new planets to be characterized, including measuring the masses. 4.51 ± 0.1 this work Mass [M ] 0 .88 ± 0.08 Nordström et al (2004) & this work In the next section we present the detection of the substellar companion orbiting HD 16760 as part of our subprogram 2 "Giant planets survey on a volume-limited sample".…”
Section: -Long-term Follow-up Of Elodie Long Period Candidatesmentioning
confidence: 99%
“…The light curve contamination of Season 2 is around 6%. Triaud et al 2013;Bouchy et al 2011b,a;Johnson et al 2011;Hellier et al 2009;Deleuil et al 2008;Winn et al 2008;Pont et al 2005Pont et al , 2006 …”
Section: Modeling Of the Data And Parameter Estimationmentioning
confidence: 99%